PENGARUH LABA DAN ARUS KAS TERHADAP HARGA SAHAM PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA - Asrianti Asrianti; Syamsuri Rahim (Jurnal Akuntansi Aktual, 2015)
The purpose of this research was to examine and find out empirical evidence of influence theinformation of earnings and cash flow on stock price. The sample used consists of 22 companies in-cluded in the group LQ 45 on period 2011–2013. Data were analyzed method using multiplelinear  regression analysis.. The results of this research showed that the regression models free of symp-toms of normality, multicolniery, autocorrelation, and heteroskedastisitas. Test results show thatthe  partial hypothesis, earnings and investing cash flow are significantly positive effect on stock prices,while operating cash flow and financing cash flow does not significantly influence on stock prices. Theresults of simultaneous hypothesis testing showed that earnings, operating cash flow, investing cashflow and financing cash flows have a significant and positive effect on stock price.Keywords:earning, cash flow, and stock price